(untitled) (City Dental College Journal, 2018)
Bruxism may lead to dental problem such as tooth wear, fracture, crack of tooth, muscles of mastication discomfort, temporomandibular joint (TMJ) dysfunction syndrome and periodontal signs such as gingival recession and tooth mobility. This article presents a case report in which bruxism caused severe tooth wear that lead to great muscular discomfort with TMJ pain. The initial treatment approach was the installation of an inter-occlusal acrylic device in centric relation of occlusion for re-establishment of the occlusal stability. Vertical dimension of occlusion, anterior guides and return of normal muscle activity were observed within 3 months. After subsiding primary symptoms, oral rehabilitation therapy was approached by means of metal bond ceramic restoration and new inter-occlusal device was provided for protection of restoration. Satisfactory aesthetics, improved function, occlusal stability were obtained after oral rehabilitation therapy. No specific trouble occurred during 1 year follow up period. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13747 City Dent. Coll. J Volume-10, Number-1, January-2013